"I Could Never Tell My Parents": Barriers to Queer Women's College Sexual Assault Disclosure to Family Members. (April 2023) - Bedera, Nicole; Nordmeyer, Kristjane; Holland, Kathryn J.
Queer women are at high risk of college sexual victimization, but they face barriers to formal support services. As a result, informal support is critical. This study uses data from 40 open-ended interviews to explore family members' reactions to queer women's disclosures and examine whether their family is a reliable source of informal support. Findings indicate that family reactions are often more harmful than helpful. In comparison to research focused on heterosexual survivors, we find family reactions to be more extreme and disparaging of queer survivors' sexual identities. In fact, family members' negative reactions may pose barriers to accessing formal services.